valuation of the reliability of levine method of wound swab for microbiological studies in chronic wounds: a pilot study. (2013)
Background: All chronic wounds habour microorganisms which may stall spontaneous healing of the wounds or impair success of wound closure. Wound biopsy for microscopy, culture and sensitivity is the preferred method of isolating microorganisms present in a wound but the procedure is resource intensive and unpleasant to patients. The aim of this paper is to evaluate the reliability of Levine swab in accurate identification of microorganisms present in a wound and identify the necessity for further studies in this regard. Methods: A semi structured questionnaire was administered and physical examination was performed on patients with chronic wounds who meet the inclusion criteria for the study. Full thickness wound biopsy and wound swab using the Levine method were taken from the wound of each patient The data generated was analysed using Statistical Package for Social Sciences (SPSS) version 20. Results: There were 21 ulcers from 19 patients but only nineteen ulcers were suitable for analysis. The mean age of the patients was 42 years (range 13-69 years). There were nine males and 10 females. Most of the ulcers were posttraumatic (67%), were located on the right side of the body and the commonest site was the right leg (24%). More than half of the ulcers had at least moderate discharge. Only one species of microorganism was isolated per wound swab or wound biopsy specimen. Comparison of results from wound swabs with wound biopsy from each of the patients revealed that isolated microorganisms were similar in 60% of cases. Conclusion: Wound swab by the Levine method may be as reliable as wound biopsy specimens for microbiological studies in chronic wounds due to certain causes. Larger studies that evaluate wounds due to different causes separately will be required to validate this observation.